Answer:
Explanation:
Given y=-1/2x-3, rewrite this as y = (-1/2)x - 3 for greater clarity.
x-intercept: Let y = 0 and find x: 0 = (-1/2)x - 3, or
(1/2)x = 3, or x = 6. Thus, (6, 0) is the x-intercept.
y-intercept: Let x = 0 and find y. Then (-1/2)(0) - 3 = y. Thus, y = -3, and the y-intercept is (0, -3).
Plot these two intercepts and then draw a line connecting them.
Example: To graph the y-intercept, start with your pencil point at the origin. Move your pencil point 3 units down and plot a dark dot there.